ASEAN'S PREPAREDNESS AND RESPONSE AGAINST HYBRID THREAT IN CYBERSPACE - Gultom, Yosua Saut Marulitua (Indonesian Association for International Relations, 2024)
This research examines ASEAN's readiness and response to threats in cyberspace. ASEAN is a region with growing internet users and a thriving economy. Unfortunately, ASEAN's cyber defense is considered low. This research uses the concept of hybrid threats by Hoffman which states that future conflicts/war create hybrid strategies, where conventional and non-conventional means are brought together to see the vulnerability. Using a descriptive study using primary and secondary data in the form of official documents, journal articles, news, and internet sources. This article found that China's rise in the cyber field, as well as the attack activities it has carried out both directly and indirectly, provide a strong threat perception for the ASEAN region. For this reason, this article concludes that ASEAN must intensify collaboration within the region and with global partners while also establishing a comprehensive cyber defense strategy, including a potential for a cyber army across the region.